MARKO JESENŠEK, 2018: PREKMURSKI JEZIK MED KNJIŽNO NORMO IN NAREČJEM: Maribor: Univerzitetna založba Univerze. - Švajncer, Marija (Slavia Centralis, 2020)
Marko Jesenšek has published a new book entitled Prekmurski jezik med knjižno normo in narečjem (2018). The monograph is the author's ninth book, in which he focuses on the Prekmurje language and proves that the Slovene language had a dual development until the formation of a unified Slovene literary norm in the middle of the 19th century.
Keywords: Marko Jesenšek; monograph; Prekmurski jezik med knjižno normo in narečjem; Prekmurian language; review